Editorial (American Journal of Islam and Society, 2006)
The “war on terror” has become one of those discursive moral high groundsthat, in reality, serve as a smokescreen to conceal the imperial ambitions of apolitical elite. While the corporate media generally supports this elite by(mis)informing the general public about the war’s “progress,” more pertinentthreats fail to attract the same kind of political attention (and general handwringing) associated with the “green menace.” I could be referring to globalwarming, which some scientists consider one of the greatest threats to humanlife, or to the spread of such deadly diseases as the H1V avian flu virus.Actually, I am referring to organized crime and its links to biker gangs.On 8 April 2006, the worst mass murder in recent Ontario historyoccurred near Shedden, a small southwestern town where the bodies of eightmen were found in a local farmer’s field. Police arrested five people, includinga Bandido motorcycle club member. The killings were club related, as thevictims were members or associate members of the club. The Bandidos are a“outlaw” biker motorcycle club, held to represent that 1 percent who engagein criminal activity. As is usually the case, this minority wreaks havoc by itsmembers’ involvement in car/motorcycle theft, drugs, prostitution, gun trafficking,and similar criminal activities. They also contribute to gun-relateddeaths and maimings, drug addiction, and theft.Given this reality, biker gang-related activities are of grave concern tocommunity health and safety. And yet the West’s public venom is mostly preservedfor Muslims, most of whom are peace-loving people seeking to livequiet productive lives in safe neighborhoods. It is this overarching discourseof the supposedly “evil” scourge of Muslims against the backdrop of themore tangible, long-term, and widespread threats of organized crime that isworrying on at least two fronts. First, its demonization of Muslims makestheir lives in the West an increasingly problematic experience and, second, itfocuses the public’s attention on an abstract threat (“terror”) while divertingattention from more tangible (if intractable) threats, thereby allowing theUnited States’ neoconservative imperial ambitions to proceed.Maligning Muslims and Islam is reaching a dangerous level of acceptabilityin the United States and elsewhere in the West, even at the level ofpolitical discourse, and is buttressed by a largely supportive general public.The result: no-fly lists, racial profiling, and the jailing and torture of Muslims ...